Performance Analysis of an Air-Based PV/T System in a Greenhouse Based on Indoor and Outdoor Test Chamber Temperature Comparison - Fiky Setiawan; Ayu Zahra Chandrasari; Tinton Dwi Atmaja; Ahmad Rajani (Journal of Environmental and Development Studies, 2026)
This study analyzes the thermal behavior of an air-based photovoltaic thermal (PV/T) system integrated with a greenhouse under tropical outdoor conditions in Bandung, Indonesia. The integration extracts excess heat from photovoltaic panels, which typically degrades electrical performance and utilizes it to modify the agricultural microclimate. The experimental setup comprised a PV/T air collector, inlet fans, a connecting outlet duct, type-K thermocouples, DHT sensors, a pyranometer, an anemometer, and a data logger. Measurements were processed at 10-minute intervals from 09:00 to 15:00 across three observation days. The analysis emphasized solar radiation, PV/T component temperatures, mass flow rate, useful heat extraction, system thermal efficiency, and the comparison between the internal greenhouse temperature (DHT5-DHT7) and the external outdoor temperature (DHT8). The empirical results demonstrated an average solar radiation ranging from 676.84 W/m² to 768.65 W/m² across the observation days. The average outlet-inlet air temperature difference ranged consistently from 5.81°C to 6.36°C. Using the measured outlet velocity and duct area, the calculated air mass flow rate was 0.0774 kg/s. Consequently, the system generated an average useful thermal output of 467.85 W and achieved an average thermal efficiency of 25.24%. This effective heat transfer resulted in the internal greenhouse temperature remaining significantly higher than the outdoor ambient temperature by an average margin of 4.05°C to 4.73°C. These findings conclusively indicate that the active PV/T hot air flow, combined with the greenhouse enclosure effect, substantially governed the thermal conditions inside the test chamber, providing a viable thermal management strategy.